Answers

2016-01-15T19:29:54+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(6x+4x-3x)/12=7
(6x+x)/12=7
7x=12*7
7x=84
x=84/7
x=12 ANS
0
2016-01-16T16:19:40+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Below is given the solution of the equation with detailed explanation of the steps :-

 \frac{x}{2} + \frac{x}{3} - \frac{x}{4} =7

find the L.C.M of the denominators and adjust it with the new denominator....

=>   \frac{6x+4x-3x}{12}=7

now simplify accordingly....

=>   \frac{(6x+4x)-3x}{12}=7

=>   \frac{10x-3x}{12}=7

=>   \frac{7x}{12}=7

change the sides to eliminate the numbers at the x, and single the x......
=>  x= \frac{7*12}{7}

the two 7's will be cut.....
=>  
x=12

and so the value of x is...
12

-----------------------------------------------------------------------------------------------------

HOPE THAT HELPS YOU!!!
PLZ MARK ANSWER AS BRAINILIEST :-)))
Or, PRESS ON "THANKS" BUTTON!!
SPEND A NICE DAY. ENJOY WORKING WITH BRAINLY :-PP

WISH YOU A HAPPY NEW YEAR AND A BEST 2016 FOR YOU!!
1 5 1